Quality Of Life After Cardiac Surgery - Mladinov, Anton (Array, 2010)
The aim of this study was to determine a health-related quality of life two or more years after a cardiac surgery using the MOS-36 item short-form health survey questionnaire. 330 members of «Croatian society of patients who underwent cardiac surgery» were asked and 196 responders, 122 men and 74 women, were included in survey, all of them more than two years after surgery and older than fifty years of age. The answers were collected by phone. Women gained better results for Physical Functioning (p<0.003) and men estimated better scores for psychical health (p<0.001). Our patients gained some different results in respect to the Croatian sample of healthy people of the same age. They declared better General Health (p<0.001), less Bodily Pain (p<0.001), but inferior Role-Emotion (p<0.001) and Social Functioning (p<0.001). The estimations of QOL improving were comparable with the results of numerous shorter follow-ups.